Root Canal Morphology of Mandibular First Premolars of Bangladeshi Population - Islam, Mohammad Aminul; Wakia, Tasnim; Alam, Md Shamsul (Update Dental College Journal, 2013)
Background: The presence of a single root canal in mandibular first premolar cannot be assumed always. The variability in canal morpholohy of root canal includes the number & shape of the canal as well as pathways of the canals. Methods: In this study, 100 mandibular first premolar teeth were evaluated by clearing technique. Collected teeth were cleaned and merged with 5.25% NaOCl for 48 hours. Then the teeth were decalcified with 5% nitric acid for 72 hours followed by dehydrated sequentially with 80-100% alcohol. After dehydration, Indian Ink was injected into the canal through the previously prepared access cavity. Finally the teeth were made transperent by 98% methylsalicylate and examined. Results: Out of 100 mandibular first premolar teeth, 89 were single rooted, 10 with double rooted and only 1 was triple. On evaluation of canal configuration according to Weine classification, mandibular first premolars had 64% type I, 5% type II, 22% type III and 9% type IV. Apical delta was found incase of 8% mandibular first premolar tooth. Conclusion: Based on this study, mandibular first premolar teeth of Bangladeshi population have multiple roots and canals and variable canal configurations. DOI: http://dx.doi.org/10.3329/updcj.v2i2.15481 Update Dent. Coll. j: 2012; 2 (2): 03-07